Three-Phase Three-Level Soft Switching Dc-Dc Converter for Industrial Applications - J. Sivavara Prasad; Y.P. Obulesh; Ch. Sai Babu (International Journal of Power Electronics and Drive Systems (IJPEDS), 2017)
In high power DC applications, the single-phase DC-DC converter will face large voltage and current stress in each control switch and thereby the power handling capacity is less. To overcome this problem, three-phase DC-DC converter is used and it is suitable for high power applications with reduced number of switches as compared with the conventional topologies. The asymmetrical duty cycle control is considered to operate the switches under soft switching and hence the switching losses are reduced. The transformer leakage inductances are used along with junction capacitances in order to form resonance and hence ZVS commutation is possible in a wider load range. The modified phase shift control method is used for the proposed converter.The operational modes and design equations of the proposed converter have been observed. The simulation is carried out with a load of 1000W for validating the proposed work.